2022
DOI: 10.37441/cejer/2022/4/1/10902
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between Sport and Leisure Activities among High School Students

Abstract: Research on the education, upbringing and habits of high school students is extremely varied and diversified across all areas of education. In our case, we would like to investigate students’ sporting and leisure habits, as several studies have found possible breakpoints in students’ lifestyles during this period, which is particularly true for sporting habits. Our research focuses on the leisure habits of students learning in Nyíregyháza and Debrecen. We were looking for answers to the following questions: Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Participants in the 10s and 60s age group were less satisfied with their leisure activities than other age groups. However, a study with adolescents showed that their satisfaction with participation in sports leisure activities was very high (22)(23). This study's contradictory results may be due to Korea's cultural background.…”
Section: Satisfaction With Participation In Sports Leisure Activitiesmentioning
confidence: 65%
“…Participants in the 10s and 60s age group were less satisfied with their leisure activities than other age groups. However, a study with adolescents showed that their satisfaction with participation in sports leisure activities was very high (22)(23). This study's contradictory results may be due to Korea's cultural background.…”
Section: Satisfaction With Participation In Sports Leisure Activitiesmentioning
confidence: 65%
“…Nowadays, with the rise of health-conscious behaviour, many people are engaging in various health-promoting preventive leisure activities. Several researches show that in addition to the entertainment function in the choice of leisure activity, the motivation to participate in sport is also an important aspect to maintain health, improve fitness and quality of life [2,16,24,28,29,32,54]. Many national and international studies report on health tourism spa and wellness services that, in addition to recreation and experience, serve to maintain and preserve health [8,26,31,37,38,40,42,43].…”
Section: Introductionmentioning
confidence: 99%